Fenomena Job Hopping Pada Gen Z Dalam Bidang Komunikasi - Geraldine Salma Sabila; Kismiyati El Karimah; Frila Nurfadila (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This research explores the phenomenon of job hopping among Gen Z in the field of communication with the aim of identifying the motives behind Gen Z's job hopping and the implications experienced by Gen Z after job hopping. The study employs a qualitative approach with the phenomenological research method. Data were collected through in-depth interviews with Gen Z individuals who have experience in job hopping in the field of communication. Additionally, interviews with human resource management experts were conducted, and literature studies were utilized to ensure data validity. The results of this study indicate that Gen Z individuals have different motives for job hopping to meet their expectations while accepting the implications of job hopping. These findings were also analyzed using Herzberg's Motivation Theory to determine the motives based on Gen Z's experiences in job hopping.